Silver(I) Complexes with Clinically Used Azoles: Synthesis, Structural Characterization and Antimicrobial Evaluation - Nevena Lj. Stevanović; Jelena Lazić; Jakob Kljun; Mia Stanković; Jasmina Nikodinovic-Runic; Iztok Turel; Miloš I. Djuran; Biljana Đ. Glišić (Medical Sciences Forum, 2022)
Recently, we synthesized silver(I) complex with the antifungal agent itraconazole, which showed improved anti-Candida potential and therapeutic safety in comparison to itraconazole and rescued zebrafish embryos affected by lethal C. albicans infection, when used in safe doses. Inspired by these results, in the present study, three new silver(I) complexes with clinically used azoles, econazole (ecz), clotrimazole (ctz) and voriconazole (vcz), [Ag(ecz)2]SbF6 (Ag1), [Ag(ctz)2]SbF6 (Ag2) and {[Ag(vcz)2]SbF6}n (Ag3) were synthesized and structurally characterized by elemental microanalysis, mass spectrometry, spectroscopy (1H NMR, IR and UV-Vis), cyclic voltammetry, molar conductivity measurements, and single crystal X-ray diffraction analysis. The spectroscopic and crystallographic results revealed that, in the synthesized silver(I) complexes, azole ligands are monodentately coordinated to the Ag(I) ion through the nitrogen atom forming [Ag(azole)2]+ complex cation. The antimicrobial effect of complexes and azole ligands was evaluated against different Candida species, as well as Gram-positive and Gram-negative bacteria. The synthesized complexes Ag1-3 exhibited good to moderate antimicrobial activity being, in most cases, more active than the corresponding azole ligands. Complexes Ag2 and Ag3 also showed strong inhibitory activity against C. albicans biofilm formation and strong inhibition of C. albicans filamentation at subinhibitory concentrations.